Initiation of asymmetric extension in continental lithosphere - Govers, R.; Wortel, M.J.R. (Tectonophysics, 1993)
Covers R. and Wortel, M.J.R., 1993. Initiation of asymmetric extension in continental lithosphere. In: M.J.R, Wortel, U. Hansen and R. Sabadini (Editors), Relationships between Mantle Processes and Geological Processes at or near the Earth's Surface. Tectonophysics, 223: 75–96. The physical conditions are investigated under which the lithospheric-scale style of extension is pure shear or simple shear. We focus on the initial stages of continental extension to monitor how symmetric or asymmetric modes of extension evolve from specific tectonic conditions. Continental collision, magma intrusions and interaction between the lithosphere and the underlying mantle are investigated as sources for extension. We use a finite element method to model the thermo-mechanical evolution of continental lithosphere. Experimental flow laws are used to model the elastic, brittle, power law creep or diffusion creep rheology of lithospheric rocks. Our results indicate that if in-plane forces change from compressive to tensile immediately after a rapid mountain building phase, initiation of a lithosphere-scale detachment fault is possible. We find a strong dependence of the extensional style on the distribution with depth of residual stresses from the collision phase. This result is consistent with observations of gravitational collapse in regions, like the Aegean and the Basin and Range Province, where detachment faults have exhumed lower crustal rocks. The predicted dip direction of the fault also agrees with observations in these areas. Intrusion of magma into continental lithosphere, which is subject to in-plane tensile forces, will cause localization of pure shear deformation. The style of deformation resulting from mantle plumes impinging to the base of the lithosphère is symmetric. Delamination of lithospheric mantle may initiate detachment faults if delamination occurs at the end of a collision phase, when in-plane forces change sign from compressive to tensile. This result also strongly depends on the assumed residual stress distribution. If delamination occurs during the mountain building phase, the style of deformation will be pure shear. Another interesting outcome from our modeling is that dramatic strain weakening as a result of a deformation mechanism change from dislocation creep to diffusion creep, reduces the tendency to strain localization.